2009
DOI: 10.1021/jp9038946
|View full text |Cite
|
Sign up to set email alerts
|

Differential Cross Sections and Product Rotational Polarization in A + BC Reactions Using Wave Packet Methods: H+ + D2 and Li + HF Examples

Abstract: The state-to-state differential cross sections for some atom + diatom reactions have been calculated using a new wave packet code, MAD-WAVE3, which is described in some detail and uses either reactant or product Jacobi coordinates along the propagation. In order to show the accuracy and efficiency of the coordinate transformation required when using reactant Jacobi coordinates, as recently proposed [ J. Chem. Phys. 2006 , 125 , 054102 ], the method is first applied to the H + D(2) reaction as a benchmark, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
99
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(119 citation statements)
references
References 110 publications
13
99
1
1
Order By: Relevance
“…For this kind of systems, it has been demonstrated that it is more efficient to use reactant Jacobi coordinates. 28 The present state-to-state reaction probabilities are calculated using a wave packet method, with the code MADWAVE3 recently reported by Zanchet et al 29 The MADWAVE3 codes based on wave packet method have been well documented in the literature 9,29 and only the details relevant to the present work will be given here. In the present calculations, the initial wave packet is located in the asymptotic reactant channel where there is no influence of the interaction potential, and the propagation grid scheme is defined using the same reactant Jacobi coordinates.…”
Section: Methodsmentioning
confidence: 99%
“…For this kind of systems, it has been demonstrated that it is more efficient to use reactant Jacobi coordinates. 28 The present state-to-state reaction probabilities are calculated using a wave packet method, with the code MADWAVE3 recently reported by Zanchet et al 29 The MADWAVE3 codes based on wave packet method have been well documented in the literature 9,29 and only the details relevant to the present work will be given here. In the present calculations, the initial wave packet is located in the asymptotic reactant channel where there is no influence of the interaction potential, and the propagation grid scheme is defined using the same reactant Jacobi coordinates.…”
Section: Methodsmentioning
confidence: 99%
“…The overall agreement found for J = 0 was accompanied by the apparent failure of the statistical predictions as J increases, a feature which, however, was due to the small number of helicity components employed in the TDWP calculation. 46 The title reaction has also been investigated by means of the SQCT approach, in combination with a variety of different theoretical methods. 47 The rate coefficients in terms of the collisional energy obtained with this quasi-classical version of the SQM approach were found to diverge from purely quasi-classical trajectory (QCT) calculations rapidly beyond E c ∼ 3 × 10 −1 eV for processes initiated from different initial rotational states of H 2 .…”
Section: Introductionmentioning
confidence: 99%
“…25 The L-shaped grid method saves a large number of grid points, as compared with a conventional rectangular grid, which makes this RCB wave packet method particularly attractive and presents an efficient alternative to the PCB approaches. [14][15][16] In 2006, Gómez-Carrasco and Roncero 26 developed an coordinate transform method to extract state-to-state information in one product channel, 27 also from the TDWP propagated in reactant Jacobi coordinates. By careful numerical testing with several reactive scattering systems, these authors reached a conclusion that their RCB method is generally more efficient than the PCB method, especially for J Ͼ 0 cases.…”
Section: Introductionmentioning
confidence: 99%